2020
DOI: 10.1364/oe.389887
|View full text |Cite
|
Sign up to set email alerts
|

Broadband graded index Gutman lens with a wide field of view utilizing artificial dielectrics: a design methodology

Abstract: A novel all-metal graded index Gutman lens is proposed. It exploits an interleaved metasurface unit-cell with glide symmetry that can provide high values of equivalent refractive index with low frequency dispersion. The result is a compact lens with broadband performance and a wide field of view up to ±70°. The proposed lens exhibits low loss, directive beams and is an appealing candidate for space applications. The design approach introduced can be applied to other graded index lenses with circular symmetry u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…The benefits of glide symmetries are not limited to holey structures. For example, glide-symmetric metallic pins also present advantages with respect to conventional pins, as demonstrated in [61], [62], [88]. Similar benefits were demonstrated in planar technologies [89]- [91].…”
Section: E Lensesmentioning
confidence: 72%
“…The benefits of glide symmetries are not limited to holey structures. For example, glide-symmetric metallic pins also present advantages with respect to conventional pins, as demonstrated in [61], [62], [88]. Similar benefits were demonstrated in planar technologies [89]- [91].…”
Section: E Lensesmentioning
confidence: 72%
“…Additionally, it has been demonstrated that glide-symmetric structures are less dispersive [12,13] and can provide a higher effective refractive index [13][14][15][16], effective permeability [17], and level of anisotropy [18], compared to their non-glide counterparts. These properties have been used to design planar lenses in [13,[19][20][21][22]. Furthermore, while the stop-band between the first two modes is suppressed in glide-symmetric structures, a large stop-band exists at higher frequency [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The eigen mode analysis is used to plot the relation between frequency and the propagation constants for Mode 1 and the effective refractive index is extracted. In [17], [40], to change the refractive index, only the height of the unit cell is varied. In the present work, the length of the diagonal extrusions (s) is varied to get the refractive index up to 1.2, and in order to further lower the refractive index, the height of the unit cell (h) is varied while fixing the diagonal corrugation at a fixed value.…”
Section: Unit Cell Design and Analysismentioning
confidence: 99%
“…The feeding and the flare studied above are now integrated with the structure of the lens designed to realize the over-all antenna structure. Some literature reported Horn antennas [40] and tapered waveguide [41] as a feed for the lens. However, feeding with tapered waveguide and horn antennas would require additional and complex waveguide to microstrip transition to integrate the rectifier at the back-end, which would reduce the design flexibility, compactness and add more demanding manufacturing tolerances as far as WPT application is concerned.…”
Section: Synthesizing the Lensmentioning
confidence: 99%